PENGARUH KEPUASAN KERJA DAN KOMITMEN ORGANISASI TERHADAP TURNOVER INTENTION PADA KARYAWAN PT. BUM DIVISI PMKS - Viniartha Seplifriskila Tampubolon; Ella Jauvani Sagala (Universitas Bunda Mulia, 2020)
A company will not run without assistance from human resources (HR). Therefore, human resources within the company generally must be maintained properly. This research was conducted on the employees of PT. Bangkitgiat Usaha Mandiri part of the Palm Oil Mill (PMKS), it is known that the level of turnover intention on employees is at a very high percentage from 2017 at 11%, 2018 at 20% and JanuarySeptember 2019 at 18%. one of the factors that can influence turnover intention itself is job satisfaction and organizational commitment felt by employees. The purpose of this study is to find out how the level of job satisfaction and organizational commitment partially and simultaneously affects the turnover intention of the employees of PT. Bangkitgiat Usaha Mandiri section of the Palm Oil Mill (PMKS). This research is a descriptive and causal research. The method used in this research is quantitative method. The research sample used was 115 respondents. Data analysis in this study used descriptive statistical analysis, normality test, multicollinearity test, heterokedasticity test, multiple regression analysis, coefficient of determination, partial hypothesis test (T test) and simultaneous (F test). The results showed that job satisfaction is high, organizational commitment is low and turnover intention is low. Tests on the coefficient of determination show that the effect of job satisfaction and organizational commitment on turnover intention of 6.8% and the remaining 93.2% are other factors not examined in this study. This study concludes that job satisfaction (X1) does not have a significant effect partially on turnover intention (Y) and organizational commitment (X2) has a significant effect partially on turnover intention (Y). In addition, job satisfaction (X1) and organizational commitment (X2) simultaneously influence (together) on turnover intention (Y).